Aktivitas Fisik sebagai Faktor yang Berhubungan dengan Indeks Massa Tubuh pada Mahasiswa - Husnul Khatimah; Fauzi Ashra; Mellia Fransiska; Andri Gemaini (Jurnal Sporta Saintika, 2026)
This study aims to analyze the relationship between physical activity and Body Mass Index (BMI) in students of the Faculty of Sports Science, Padang State University. This study used a quantitative design with a cross-sectional approach involving 140 students as respondents. The variables analyzed included age, BMI, and physical activity level measured using MET-min/week units. Normality test was conducted using Kolmogorov-Smirnov, while relationship and contribution analysis were conducted through correlation and regression tests. Normality test results showed that BMI and physical activity variables were not normally distributed (p < 0.05). Correlation analysis showed a relationship between physical activity and BMI, with the strength of the relationship classified as [weak/moderate], with a significance value of p < 0.05. Regression analysis showed that physical activity contributed [R² %] to the variation in BMI. This finding indicates that although physical activity has a relationship with BMI, other factors outside of physical activity also play a role in determining the anthropometric status of sports students. The results of this study provide an empirical picture of the characteristics of physical activity and BMI in sports students and can be the basis for developing fitness and health monitoring strategies in the University environment.